2021
DOI: 10.1094/pdis-04-20-0798-re
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Trunk Pathogens in South African Olive Nurseries

Abstract: Several fungal trunk pathogens are associated with olive trunk diseases in South Africa. Little is known regarding the inoculum sources of these pathogens in the olive industry and no specific management strategies are in place. The aim of this study was to investigate the status of olive nurseries in South Africa, with regard to the presence of trunk pathogens in olive plant material, to determine whether nursery material can be considered inoculum sources contributing to long distance dispersal of these path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Phylogenies were viewed in FigTree v. 1.4.2 ( http://tree.bio.ed.ac.uk/software/figtree/ ). For a limited number of isolates, species were identified using species-specific PCR ( Diaporthe foeniculina according to Lesuthu et al 2019 and the new species of Pseudophaeomoniella according to Van Dyk 2020 ), DNA fingerprinting ( Botryosphaeriaceae according to the protocols of Alves et al 2007 ), or the morphology was compared to isolates that had been identified using molecular techniques. Representatives of all recovered species were included in phylogenetic analyses to confirm the inferred identities.…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenies were viewed in FigTree v. 1.4.2 ( http://tree.bio.ed.ac.uk/software/figtree/ ). For a limited number of isolates, species were identified using species-specific PCR ( Diaporthe foeniculina according to Lesuthu et al 2019 and the new species of Pseudophaeomoniella according to Van Dyk 2020 ), DNA fingerprinting ( Botryosphaeriaceae according to the protocols of Alves et al 2007 ), or the morphology was compared to isolates that had been identified using molecular techniques. Representatives of all recovered species were included in phylogenetic analyses to confirm the inferred identities.…”
Section: Methodsmentioning
confidence: 99%
“…endophytic phases for these fungi, as they have been isolated from asymptomatic mother plants and propagation material (Halleen et al, 2003;Aroca et al, 2010;Berlanas et al, 2020;van der Merwe et al, 2021). Several studies have confirmed that plant propagation stages are potential infection points in grapevine nurseries (Edwards and Pascoe 2004;Aroca et al, 2010;Halleen et al, 2003;2007a;Agustí-Brisach et al, 2013), and recent studies indicate the role of infected planting material in the dissemination of fungal trunk pathogens in stone fruit trees (Marín-Terrazas et al, 2016;van Dyk et al, 2021a;van der Merwe et al, 2021;Capote et al, 2022) and apple (Havenga et al, 2019).…”
Section: A C D Bmentioning
confidence: 90%
“…Crop intensification is also likely to disturb microflora balances in agro-ecosystems, promoting transfer of trunk pathogens and their adaptation to new woody hosts. In recent years, emergence of new FTD has been shown for several woody crops (Damm et al, 2010;Markakis et al, 2017;van der Merwe et al, 2021;van Dyk et al, 2021a;.…”
Section: Crop Intensificationmentioning
confidence: 99%
“…There are several species from the Phaeoacremonium genus associated with olive diseases worldwide: Phaeoacremonium africanum [8,9], P. alvesii [10], P. italicum [10][11][12], P. minimum [8][9][10][11][12][13][14], P. oleae [8,9], P. parasiticum [8][9][10][11]15], P. prunicola [8,9], P. scolytii [8][9][10][11][12], P. spadicum [8,9], and P. sicilianum [10,11]. P. iranianum is a specie from the family Togniniaceae, named after the country, Iran, from which the majority of strains were collected [6].…”
Section: Discussionmentioning
confidence: 99%